Penanganan Kognitif Down Syndrome melalui Metode Puzzle pada Anak Usia Dini - Rusdial Marta (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
Down syndrome children are able to speak well, but in delivering the vocabulary is still lacking, they generally have difficulty thinking abstract. Learning process, especially cognitive, thinking aspects such as remembering, understanding, evoking, differentiating, finding and applying the meanings contained in a learning is very difficult to be done by the child's Down syndrome. One of the media that can be used in learning that is the method of puzzle, which makes them interested, so they feel no coercion, accept the material easily, not bored, with these methods can improve cognitive abilities. The purpose of this study is to describe Cognitive Handling of Down Syndrome Children Through Puzzle Method. The research method used in this study is a literature review that links research with existing literature and fill the gap in previous research. The results obtained in this study the use of puzzle methods can improve the cognitive child.Keywords: Cognitive, Down syndrome , puzzle